Relationship between perceived social support and self-care behavior in type 2 diabetics: A cross-sectional study - Siamak Mohebi; Mahmoud Parham; Gholamreza Sharifirad; Zabihollah Gharlipour; Abolfazl Mohammadbeigi; Fatemeh Rajati (Wolters Kluwer Medknow Publications, 2018)
Background: Social support is one of the most effective factors on the diabetic self-care. This study aimed to assess social support and its relationship to self-care in type 2 diabetic patients in Qom, Iran. Study Design: A cross-sectional study was conducted on 325 diabetics attending the Diabetes Mellitus Association. Methods: Patients who meet inclusion and exclusion criteria were selected using random sampling method. Data were collected by the Summary of Diabetes Self-Care Activities and Multidimensional Scale of Perceived Social Support, with hemoglobin A1C test. Data were analyzed using descriptive statistics and independent t-test, analysis of variance, Pearson correlation, and linear regression test, using 0.05 as the critical significance level, provided by SPSS software. Results: The mean and standard deviation of self-care and social support scores were 4.31 ± 2.7 and 50.32 ± 11.09, respectively. The mean level of glycosylated hemoglobin (HbA1C) of patients was 7.54. There was a significant difference between mean score of self-care behaviors and social support according to gender and marital status (P < 0.05). The regression analysis showed that disease duration was the only variable which had a significant effect on the level of HbA1C (P < 0.001). Pearson correlation coefficient indicated that self-care and social support significantly correlated (r = 0.489, P > 0.001) and also predictive power of social support was 0.28. Self-care was significantly better in diabetics with HbA1C ≤7%. Patients who had higher HbA1C felt less, but not significant, social support. Conclusions: This study indicated the relationship between social support and self-care behaviors in type 2 diabetic patients. Interventions that focus on improving the social support and self-care of diabetic control may be more effective in improving glycemic control.